Environment-friendly rubber nano composite material for tires
By using nano-microcrystalline cellulose in tire materials instead of carbon black and white carbon black, combined with silane coupling agent, the problem of increasing tire hardness and modulus is solved, and the environmental protection performance and service life are improved, while reducing the temperature and loss. Carbon footprint.
Patent Information
- Application Number
- CN202411606411.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-03
AI Technical Summary
While increasing hardness and modulus, existing tire materials are difficult to reduce irreversible deformation losses, and there are problems of high energy consumption and environmental pollution during the production process.
Nanomicrocrystalline cellulose is used to replace traditional carbon black as filler, and white carbon black is prepared by precipitation method, combined with silane coupling agent, to improve the reinforcement and environmental protection performance of rubber composite materials.
It significantly reduces irreversible deformation loss, improves the tensile resistance, wear resistance and tear strength of the tire, reduces the carbon footprint during the production process, and extends the service life of the tire.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber, in particular to an environmentally friendly rubber nanocomposite material for tires. Background Art
[0002] Rubber has become an important material in people's daily life due to its special property of high elasticity. However, with the improvement of the quality of life, people's requirements for the various properties and costs of rubber products are also gradually increasing. Therefore, fillers are usually used to reinforce rubber to achieve this purpose. Carbon black is the most important reinforcing filler in the rubber industry. To date, carbon black, as the most traditional rubber reinforcing agent, is still widely used in the production and manufacturing of rubber products such as tires, and has an irreplaceable position. However, it is undeniable that the disadvantages of carbon black as a reinforcing filler are also more significant, such as dependence on oil, large processing pollution, high energy consumption, single color, etc., and it takes at least 200 years for waste rubber to decompose to the point where it does not affect the growth of vegetation in the soil. Therefore, waste rubber poses a great threat to environmental deterioration, vegetation growth and human health.
[0003] Since biomass is currently the most widely used renewable energy source, and its content is very high and degradable, researchers have turned their attention to biomass materials and studied their application in rubber. Cellulose belongs to biomass materials and is the most abundant natural renewable, degradable and pollution-free polymer in nature. It is widely present in animals, plants and bacteria. Waste paper contains a large amount of cellulose, and the price is low and the amount of waste paper is large, so it is a very attractive and excellent fiber resource.
[0004] In view of the shortcomings of carbon black, a commonly used reinforcing filler for rubber, such as high dependence on petrochemicals, high energy consumption, and large processing pollution, the excellent properties of nano-microcrystalline cellulose make it have a certain reinforcing effect on rubber. For many years, our research group has been exploring the extraction of various nano-microcrystalline cellulose from different raw materials and using them to partially replace carbon black and white carbon black to reinforce rubber, thereby reducing the amount of carbon black, reducing costs, and saving resources.
[0005] We disclose an environmentally friendly rubber nanocomposite material for tires. Nanocrystalline cellulose is prepared by hydrolyzing industrial microcrystalline cellulose, and it is used as a filler to partially replace carbon black to reinforce natural rubber. A rubber composite material with excellent comprehensive performance can be prepared to reach the level of industrial fillers.
[0006] The existing defects are:
[0007] 1. Patent document CN101885862B discloses a rubber nano-short fiber composite material for automobile tires and a preparation method thereof. "The present invention relates to a rubber nano-short fiber composite material for automobile tires and a preparation method thereof. Needle-shaped silicate is modified by a CO2 supercritical method, and is dissociated into nano-short fibers during mixing with a rubber matrix. Soft carbon black is added at the same time. The prepared composite material is used as an automobile tire apex, and has the characteristics of high hardness, high modulus, and low heat generation, and also has excellent processing performance." The rubber nano-short fiber composite material for automobile tires and a preparation method thereof in the above-mentioned public document mainly considers how to prepare a tire apex with the characteristics of high hardness, high modulus, and low heat generation, which is not convenient for reducing the energy lost by irreversible deformation and is difficult to improve its service life.
[0008] 2. Patent document CN116178801A discloses a low rolling resistance and low temperature rise tire tread rubber material and a preparation method thereof. "The present invention relates to the field of tires, and specifically to a low rolling resistance and low temperature rise tire tread rubber material and a preparation method thereof, comprising the following components in parts by weight: 0-50 parts of 1,4-trans polyisoprene rubber, 0-100 parts of natural rubber, 10-60 parts of silica, 0-100 parts of carbon black, 0-80 parts of white carbon black, 0-20 parts of silane coupling agent, 1-5 parts of stearic acid, 1-5 parts of zinc oxide, 1-3 parts of antioxidant, and 1-4 parts of accelerator. , 1 to 5 parts of cyclohexane oil, and 1 to 4 parts of sulfur. Compared with the prior art, the tire tread rubber of the present invention adopts 1,4-trans polyisoprene rubber and natural rubber as the base rubber, silica, carbon black and white carbon black as composite fillers, and other auxiliary materials, which effectively reduces the rolling resistance and dynamic temperature rise of the rubber, and has good wear resistance and physical and mechanical properties. "The low rolling resistance and low temperature rise tire tread rubber material and its preparation method in the above-mentioned public documents mainly consider how to effectively reduce the rolling resistance and dynamic temperature rise of the rubber, which is not convenient for reducing the carbon footprint in the tire production process;
[0009] 3. Patent document CN106279839A discloses a method for manufacturing a high-grip and shear-hardened rubber composite material for tires. "The present invention discloses a method for manufacturing a high-grip and shear-hardened rubber composite material for tires, and the specific steps are as follows: ① using the existing open mixing technology to add the rubber mixture to the rubber open mixing mill, ② adding a rubber foaming agent to the mixture obtained in step ①, ③ adding a shear thickening material to the mixture in step ②, ④ extruding the mixture obtained in step ③ through a screw extruder to obtain the present invention. When the tire rotates at a low speed, the shear thickening material in the rubber / shear thickening composite material The thickening material can flow and deform, causing the rubber / shear thickening composite material to deform greatly, resulting in the rubber / shear thickening composite material becoming softer and increasing the tire's grip; conversely, the tire's rolling resistance can be reduced by rotating the tire quickly. Adding environmentally friendly aromatic hydrocarbon oil and oil-extended styrene-butadiene rubber to the formula can increase the elasticity of the rubber and the softness of the molecular chain, increase the ground contact area, and thus improve the tire's grip. The manufacturing method of the high-grip and shear-hardened tire rubber composite material in the above-mentioned public document mainly considers how to increase the ground contact area to improve the tire's grip, but is not convenient for improving the tire's tear strength and low heat generation effect. Summary of the invention
[0010] The object of the present invention is to provide an environmentally friendly rubber nanocomposite material for tires to solve the technical problems raised in the above background technology.
[0011] To achieve the above object, the present invention provides the following technical solution: an environmentally friendly rubber nanocomposite material for tires, characterized in that: the rubber nanocomposite material is prepared by mixing the following raw materials based on 100 parts by weight of the raw rubber component:
[0012] 100.0 parts of natural rubber;
[0013] Carbon black 10.0-90.0 parts;
[0014] 1.0-80.0 parts of white carbon black;
[0015] Nano-microcrystalline cellulose 1.0-20.0 parts;
[0016] 1.0-20.0 parts of operating oil;
[0017] Silane coupling agent 1.0-8.0 parts;
[0018] And appropriate amounts of vulcanizers, accelerators, activators and antioxidants.
[0019] Furthermore, the rubber nanocomposite material is prepared by mixing the following raw materials:
[0020] 100.0 parts of natural rubber;
[0021] Carbon black 10.0-80.0 parts;
[0022] 1.0-60.0 parts of white carbon black;
[0023] Nanocrystalline cellulose 5.0-20.0 parts
[0024] Silane coupling agent 2.0-6.0 parts;
[0025] Antiaging agent 1.0-4.0 parts;
[0026] 1.0-5.0 parts of active agent;
[0027] Accelerator 1.0-4.0 parts;
[0028] Vulcanizing agent 1.0-5.0 parts.
[0029] Furthermore, the white carbon black is prepared by a precipitation method, and the BET specific surface area is 100-200m 2 / g, carbon black particle size is 20-40nm.
[0030] Furthermore, the active agent is zinc oxide and stearic acid, wherein zinc oxide is 1.0-4.0 parts, stearic acid is 1.0-3.0 parts, the vulcanizing agent is 1.0-5.0 parts of sulfur, and the accelerator is accelerator CZ, accelerator DPG and accelerator DM, wherein accelerator DM is 0.2-2.0 parts, accelerator DPG is 0.1-2.0 parts, and accelerator CZ is 0.2-2.0 parts.
[0031] Further, the mixing steps of the environmentally friendly rubber nanocomposite material for the tire are as follows:
[0032] S1, one-stage mixing: mixing is performed using an internal mixer, first adding natural rubber, pressing down the mass and holding it for 55-65 seconds, then raising the mass, adding white carbon black, carbon black, nano-microcrystalline cellulose, silane coupling agent, activator and antioxidant, pressing down the mass again and holding it for 55-65 seconds, raising the mass to add carbon black and rubber operating oil, pressing down the mass and holding it for 80-100 seconds, raising the mass, and cleaning it;
[0033] S2, two-stage mixing: use an open mill for mixing, discharge the rubber compound after internal mixing onto the open mill, adjust the roller distance of the double-roll open mill to 0.8-1.2mm, so that the rubber compound is coated on the roller, add accelerator and vulcanizer in turn, cut the left and right knives three times each, when the roller distance is adjusted to 0.15-0.25mm, perform the triangle wrapping operation five times, and finally adjust the roller distance to 1.5-2.0mm, unload the sheet and park for standby use.
[0034] Furthermore, the environmentally friendly rubber nanocomposite material for tires is used in preparing tire treads.
[0035] Furthermore, a tire, wherein the tire tread is prepared by vulcanizing the environmentally friendly rubber nanocomposite material for tires as claimed in claim 6.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] 1. The present invention uses precipitated silica, carbon black and nano-microcrystalline cellulose as reinforcing fillers, which has high reinforcing properties. As the amount of nano-microcrystalline cellulose replacing carbon black increases, the viscosity modulus gradually decreases. The reason is that the waste paper nano-microcrystalline cellulose is polar, while natural rubber is non-polar, so the compatibility of the waste paper nano-microcrystalline cellulose with the rubber matrix is poor. The addition of the nano-microcrystalline cellulose reduces the networking of the filler, reduces the energy loss of irreversible deformation, and thus improves the service life of the prepared tire;
[0038] 2. The nano-microcrystalline cellulose used in the preparation of the rubber nanocomposite material in the present invention is beneficial to reducing the environmental pollution in the traditional tire manufacturing and improving the environmental performance of the tire. As a natural polymer material, the nano-microcrystalline cellulose has the characteristics of being renewable and degradable, which helps to reduce the carbon footprint in the tire production process;
[0039] 3. Through reasonable proportioning, the rubber nanocomposite material of the present invention not only ensures the basic physical properties of the tire, but also significantly improves the tire's tensile strength, wear resistance, tear strength and low heat generation effect. Through the synergistic effect of white carbon black and carbon black, and the addition of silane coupling agent, the interfacial bonding force between rubber and filler is effectively enhanced, thereby improving the overall performance of the tire. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Embodiment 1: An embodiment provided by the present invention: an environmentally friendly rubber nanocomposite material for tires, the formula including the following components and their mass fractions: 100 parts of natural rubber, 40 parts of carbon black, 25 parts of white carbon black, 5 parts of nano-microcrystalline cellulose, 15 parts of rubber operating oil, 2 parts of stearic acid, 1 part of antioxidant, 4 parts of silane coupling agent, 2.13 parts of resin, 3 parts of zinc oxide, 1.5 parts of paraffin, 1 part of accelerator DPG, 1 part of accelerator DM, 0.5 parts of accelerator CZ, and 2 parts of oil-extended sulfur.
[0042] Embodiment 2: An embodiment provided by the present invention: an environmentally friendly rubber nanocomposite material for tires, the formula including the following components and their mass fractions: 100 parts of natural rubber, 35 parts of carbon black, 25 parts of white carbon black, 10 parts of nano-microcrystalline cellulose, 15 parts of rubber operating oil, 2 parts of stearic acid, 1 part of antioxidant, 4 parts of silane coupling agent, 2.13 parts of resin, 3 parts of zinc oxide, 1.5 parts of paraffin, 1 part of accelerator DPG, 1 part of accelerator DM, 0.5 parts of accelerator CZ, and 2 parts of oil-extended sulfur.
[0043] Example 3: An embodiment provided by the present invention: an environmentally friendly rubber nano-composite material for tires, the formula including the following components and their mass fractions: 100 parts of natural rubber, 30 parts of carbon black, 25 parts of white carbon black, 15 parts of nano-microcrystalline cellulose, 15 parts of rubber operating oil, 2 parts of stearic acid, 1 part of antioxidant, 4 parts of silane coupling agent, 2.13 parts of resin, 3 parts of zinc oxide, 1.5 parts of paraffin, 1 part of accelerator DPG, 1 part of accelerator DM, 0.5 parts of accelerator CZ, and 2 parts of oil-extended sulfur.
[0044] Example 4: An embodiment provided by the present invention: an environmentally friendly rubber nano-composite material for tires, the formula including the following components and their mass fractions: 100 parts of natural rubber, 25 parts of carbon black, 25 parts of white carbon black, 20 parts of nano-microcrystalline cellulose, 15 parts of rubber operating oil, 2 parts of stearic acid, 1 part of antioxidant, 4 parts of silane coupling agent, 2.13 parts of resin, 3 parts of zinc oxide, 1.5 parts of paraffin, 1 part of accelerator DPG, 1 part of accelerator DM, 0.5 parts of accelerator CZ, and 2 parts of oil-extended sulfur.
[0045] Comparative Example 1: An embodiment provided by the present invention: an environmentally friendly rubber nanocomposite material for tires, the formula including the following components and their mass fractions: 100 parts of natural rubber, 45 parts of carbon black, 25 parts of white carbon black, 15 parts of rubber operating oil, 2 parts of stearic acid, 1 part of antioxidant, 4 parts of silane coupling agent, 2.13 parts of resin, 3 parts of zinc oxide, 1.5 parts of paraffin, 1 part of accelerator DPG, 1 part of accelerator DM, 0.5 parts of accelerator CZ, and 2 parts of oil-extended sulfur.
[0046] Comparative Example 2: An embodiment provided by the present invention: an environmentally friendly rubber nanocomposite material for tires, the formula including the following components and their mass fractions: 100 parts of natural rubber, 50 parts of carbon black, 10 parts of white carbon black, 15 parts of rubber operating oil, 2 parts of stearic acid, 1 part of antioxidant, 2 parts of silane coupling agent, 2.13 parts of resin, 3 parts of zinc oxide, 1.5 parts of paraffin, 1 part of accelerator DPG, 1 part of accelerator DM, 0.5 parts of accelerator CZ, and 2 parts of oil-extended sulfur.
[0047] The specific steps of the synthesis method of nanocrystalline cellulose used in Examples 1-4 are as follows:
[0048] Weighed sodium hydroxide and surfactant sodium dodecylbenzene sulfonate are prepared into a solution, weighed waste paper is crushed and soaked in the prepared solution for 2 hours, centrifuged and stirred after 2 hours at a speed of 10000r / min, the obtained waste paper fibers are washed, and then the obtained waste paper fibers are dried to obtain pure waste paper fibers, which are crushed for standby use, sulfuric acid solution with a mass concentration of 59% is added to the waste paper fibers, heated in a water bath, stirred to obtain an acidified suspension, the obtained suspension is diluted 10 times, filtered and washed to neutrality, freeze-dried, and finally waste paper-based nano-microcrystalline cellulose is obtained.
[0049] The formulas of the embodiments, comparative examples and reference examples are shown in Table 1 (parts by weight)
[0050] Table 1
[0051]
[0052]
[0053] Table 1 footnotes:
[0054] *1: SCR20, a product of Hainan Sinochem;
[0055] *2: N234, Cabot Chemicals;
[0056] *3: 1165MP, product of Solvay Fine Chemical Additives (Qingdao) Co., Ltd.;
[0057] *5: V500, product of Ningbo Hansheng Co., Ltd.
[0058] *6: Stearic acid, a product of Yihai Kerry;
[0059] *7: Antioxidant 4020 (6PPD), a product of Sinopec Nanjing Chemical Industry Co., Ltd.; *8: Si69, a product of Evonik Chemicals;
[0060] *9: C5 / C9 resin, ExxonMobil product;
[0061] *10: Zinc oxide, product of Qingdao Haiyan Chemical Co., Ltd.;
[0062] *11: Microcrystalline wax, a product of Yanggu Huatai;
[0063] *12: Accelerator DPG, a product of Shandong Shangshun Chemical Co., Ltd.;
[0064] *13: Accelerator DM, a product of Shandong Shangshun Chemical Co., Ltd.;
[0065] *14: Propellant accelerator, product of Shandong Shangshun Chemical Co., Ltd.;
[0066] *15: Oil-filled sulfur powder, a product of Wuxi Huasheng Rubber New Material Technology Co., Ltd.
[0067] Performance Testing:
[0068] Vulcanization characteristics: According to GB / T 9869-1997 standard, the UR-2030 rotorless vulcanizer produced by Taiwan Uni-Con Company was used to measure the vulcanization curve and vulcanization characteristic parameters at 143°C and a swing angle of 1°.
[0069] Tensile properties: The tensile strength and tear strength of the rubber nanocomposites are in accordance with GB / T 528-2009 and GB / T529-2008 standards. The tensile specimen is dumbbell-shaped and the tearing specimen is right-angled. The test is performed using a U-CAN UT-2060 electronic tensile testing machine at a rate of 500 mm / min.
[0070] Abrasion test: According to GB / T 1689-1998 standard, the wear amount of the material was tested using the GOTECH GT-7012-A Akron abrasion tester produced by the High Speed Rail Company.
[0071] Heat generation performance: The compression fatigue heat generation performance of the material was tested according to GB / T 15584-1995 standard. The testing instrument was U-CAN UD-3801 compression fatigue heating tester. The test conditions were frequency 30Hz, strain double amplitude 5.71mm, load force 24.5Kg, test time 25min, and the test specimen was a cylinder with a height of 25mm and a diameter of 17.8mm.
[0072] Performance test data is shown in Table 2:
[0073] Table 2
[0074]
[0075] It can be seen from Table 2 that Example 1 is the best example with the best comprehensive performance. It can be seen that after the addition of nano-microcrystalline cellulose, Example 1 has higher strength and higher elongation at break, while the wear does not decrease significantly, especially the compression heat generation is significantly reduced, which is beneficial to reducing fuel consumption and increasing the service life of the tire.
[0076] Working principle: by using precipitated silica, carbon black and nano-microcrystalline cellulose as reinforcing fillers, it has high reinforcement. As the amount of nano-microcrystalline cellulose replacing carbon black increases, the viscosity modulus gradually decreases. The reason is that waste paper nano-microcrystalline cellulose is polar, while natural rubber is non-polar. Therefore, the compatibility of waste paper nano-microcrystalline cellulose with the rubber matrix is poor. Its addition reduces the networking of the filler, which reduces the energy loss of irreversible deformation. The nano-microcrystalline cellulose selected in the preparation of rubber nano-composite materials is conducive to reducing the pollution to the environment in traditional tire manufacturing and improving the environmental performance of tires. Nano-microcrystalline cellulose, as a natural polymer material, has the characteristics of renewable and degradable, which helps to reduce the carbon footprint in the tire production process. Through reasonable proportioning, the rubber nano-composite material not only ensures the basic physical properties of the tire, but also significantly improves the tensile strength, wear resistance, tear strength and stability of the tire. Through the synergistic effect of white carbon black and carbon black, and the addition of silane coupling agent, the interfacial bonding force between rubber and filler is effectively enhanced, thereby improving the overall performance of the tire.
[0077] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. An environmentally friendly rubber nanocomposite material for tires, characterized in that: The rubber nanocomposite material is prepared by mixing the following raw materials based on 100 parts by weight of the natural rubber component: 100.0 parts of natural rubber; Carbon black 10.0-90.0 parts; 1.0-80.0 parts of white carbon black; Nano-microcrystalline cellulose 1.0-20.0 parts; 1.0-20.0 parts of operating oil; Silane coupling agent 1.0-8.0 parts; And appropriate amounts of vulcanizers, accelerators, activators and antioxidants.
2. The environmentally friendly rubber nanocomposite material for tires according to claim 1, characterized in that: The rubber nanocomposite material is prepared by mixing the following raw materials: 100.0 parts of natural rubber; Carbon black 10.0-80.0 parts; 1.0-60.0 parts of white carbon black; Nanocrystalline cellulose 5.0-20.0 parts Silane coupling agent 2.0-6.0 parts; Antiaging agent 1.0-4.0 parts; 1.0-5.0 parts of active agent; Accelerator 1.0-4.0 parts; Vulcanizing agent 1.0-5.0 parts.
3. The environmentally friendly rubber nanocomposite material for tires according to claim 2, characterized in that: The white carbon black is prepared by precipitation method, and the BET specific surface area is 100-200m 2 / g, carbon black particle size is 20-40nm.
4. The environmentally friendly rubber nanocomposite material for tires according to claim 2, characterized in that: The active agent is zinc oxide and stearic acid, wherein zinc oxide is 1.0-4.0 parts, stearic acid is 1.0-3.0 parts, the vulcanizing agent is 1.0-5.0 parts of sulfur, and the accelerator is accelerator CZ, accelerator DPG and accelerator DM, wherein accelerator DM is 0.2-2.0 parts, accelerator DPG is 0.1-2.0 parts, and accelerator CZ is 0.2-2.0 parts.
5. A mixing method for an environmentally friendly rubber nanocomposite material for tires according to claims 1-4, characterized in that: The mixing steps of the environmentally friendly rubber nanocomposite material for the tire are as follows: S1, one-stage mixing: mixing is performed using an internal mixer, first adding natural rubber, pressing down the mass and holding it for 55-65 seconds, then raising the mass, adding white carbon black, carbon black, nano-microcrystalline cellulose, silane coupling agent, activator and antioxidant, pressing down the mass again and holding it for 55-65 seconds, raising the mass to add carbon black and rubber operating oil, pressing down the mass and holding it for 80-100 seconds, raising the mass, and cleaning it; S2, two-stage mixing: use an open mill for mixing, discharge the rubber compound after internal mixing onto the open mill, adjust the roller distance of the double-roll open mill to 0.8-1.2mm, so that the rubber compound is coated on the roller, add accelerator and vulcanizer in turn, cut the left and right knives three times each, when the roller distance is adjusted to 0.15-0.25mm, perform the triangle wrapping operation five times, and finally adjust the roller distance to 1.5-2.0mm, unload the sheet and park for standby use.
6. The environmentally friendly rubber nanocomposite material for tires according to claims 1-4, characterized in that: The environmentally friendly rubber nanocomposite material for tires is used in preparing tire treads.
7. A tire, characterized in that: The tire tread is prepared by vulcanizing the environmentally friendly rubber nanocomposite material for tires as claimed in claim 6.